The Role of the Indonesian National Armed Forces (TNI) in Supporting Regional Development Acceleration in Papua - Jorry S Koloay; Antonius W; G. Luky (Journal Research of Social Science, Economics, and Management, 2024)
The conflict in Papua has evolved into an increasingly complex situation, with the separatist movement led by the Free Papua Organization (OPM) seeking to break away from Indonesia. This study examines the role of the Indonesian National Armed Forces (TNI) in supporting the acceleration of regional development in Papua amidst the ongoing conflict involving the Free Papua Organization (OPM). The primary objective is to analyze the TNI’s use of a "smart power" strategy that combines soft, hard, and diplomatic approaches to address security challenges while promoting socio-economic development. Employing a qualitative research method, this study gathers data through in-depth interviews, case studies, and secondary sources, including reports, documents, and media coverage. The results indicate that the TNI’s operations significantly contribute to infrastructure development, human resource improvement, and basic service delivery in Papua, despite persistent security threats from OPM. Strategies such as territorial engagement, community empowerment, and inclusive social communication have proven effective in mitigating conflict impacts. The findings also highlight the challenges posed by international narratives on human rights violations, requiring a balanced approach that fosters local trust and international accountability.